2018
DOI: 10.1186/s12937-018-0412-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rye-based evening meals on cognitive functions, mood and cardiometabolic risk factors: a randomized controlled study in healthy middle-aged subjects

Abstract: BackgroundWhole grain (WG) intake is associated with reduced risk of obesity, type 2 diabetes and cardiovascular disease, whereas type 2 diabetes increases the risk of cognitive decline and dementia. The purpose of this study was to investigate the effects of short-term intervention with WG rye on cognitive functions, mood and cardiometabolic risk markers in middle-aged test subjects.MethodRye-based breads were provided to 38 healthy test subjects (aged 52-70y) during three consecutive days in a crossover stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 53 publications
1
32
0
1
Order By: Relevance
“…commonly in both human trials and animal studies involving oat and rye DF supplementation. [9,42] The protective effects of SCFAs on the intestinal epithelial cells are well established and their increased synthesis in the presence of DF was observed in our study and in previous reports. [18,43,44] We postulate that a low-fiber WD potentially led to increased activity to produce and thus to increase serum 5-HT levels, and decrease alternative (protective) pathways for TRP metabolism, possibly via mechanisms involving SCFAs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…commonly in both human trials and animal studies involving oat and rye DF supplementation. [9,42] The protective effects of SCFAs on the intestinal epithelial cells are well established and their increased synthesis in the presence of DF was observed in our study and in previous reports. [18,43,44] We postulate that a low-fiber WD potentially led to increased activity to produce and thus to increase serum 5-HT levels, and decrease alternative (protective) pathways for TRP metabolism, possibly via mechanisms involving SCFAs.…”
Section: Discussionsupporting
confidence: 83%
“…[3][4][5] Human interventions and observational studies suggest that a fiber-rich diet is linked to lower body weight, improved insulin sensitivity and glucose responses, and reduced blood cholesterol. [6][7][8][9][10] DF can modulate cholesterol metabolism. [11,12] Furthermore, whole-grain fiber-rich diets induce clinical improvements related to bile acid (BA) metabolism and synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation with high amylose-resistant starch has been shown to reduce body fat, increase levels of acetate, early-phase insulin, and glucagon-like peptide- (GLP-) 1, and increase the number of gut microbes that produced acetate in volunteers with normal body weight [ 53 ]. Rye-based bread supplemented with resistant starch type 2 increased insulin sensitivity, fasting levels of peptide YY (PYY), GLP-2, acetate, butyrate, and total SCFAs in healthy middle-aged individuals [ 54 ]. Furthermore, administration of dietary fiber in T2DM patients enhanced a group of SCFA producers and improved glycated hemoglobin levels, partly via increased GLP-1 production, which resulted in T2DM alleviation [ 13 ].…”
Section: Beneficial Effects Of Scfas On Energy and Glucose Homeostmentioning
confidence: 99%
“…On the other hand, a short-term (three days) intervention with ryebased bread did not change working memory and attention. 97 By reviewing the available literature, a gap in studies investigating the impact of dietary fiber on cognition was identified. Most studies to date focus on mental health (particularly depression) in relation to dietary fiber intake.…”
Section: Evidence From Interventional Studiesmentioning
confidence: 99%
“…On the other hand, a short-term (three days) intervention with rye-based bread did not change working memory and attention. 97…”
Section: Dietary Fiber and Cognition: What Do We Know?mentioning
confidence: 99%